Evaluation of Drug Dosing in Renal Failure - Hammad, Mohamed A.; Khamis, Ahmed A.; Al-Akhali, Khaled M.; Ali, Tarek M.; Alasmri, Ashwag M.; Al-Ahmari, Eman M.; Mossa, Enas M; Al-Gahtani, Nada M.; El-Sobky, Yasmin (International Organization of Scientific Research (IOSR), 2016)
Introduction: Rapid accumulation and toxicity can be developed if drugs dosages are not adjusted in patients with chronic kidney diseases (CKD). Objectives: To evaluate the prevalence of correct dosing in chronic kidney diseases depending on renal function estimation. Study Design: A cross-sectional observational study involving patients in medical ward from January to July 2014 at Aseer Central Hospital in Abha, Kingdom of Saudi Arabia Methods: Demographic data were collected from patients, patients' files and healthcare providers. Dosage adjustment depends on the patients’ kidney function, most often estimated by the patient's glomerular filtration rate (eGFR) calculated by the CKD-EPI (Chronic Kidney Disease Epidemiology Collaboration) and a computerized system was used to determine the adjusted renal dose. Results: From total 2470 prescribed drugs for 500 inpatients, 420 (17%) drugs need a dosing adjustment in chronic renal failure and 2050 (83%) drugs do not need. From the 420 drugs that need a dosing adjustment, the dose of 202 (48.1%) drugs were adjusted, and of 218 (51.9%) drugs were not. Drugs that need a readjustment are allopurinol, ampicillin, cefepime, cefixime, ceftazidime, ceftriaxone, gentamycin, levofloxacin, meropenem, metoclopramide, metronidazole, ranitidine, rosuvastatin, tazocin, tienam and vancomycin. Conclusions: The dosing of more than half of the medications that need dosing adjustment in CKD were not adjusted which can increase the side effects and toxicity of these drugs for CKD patients. It is the pharmacist duty by co-operation with the medical team to ensure the prescribing of optimal dose. Keywords: Aseer Central Hospital, Chronic kidney disease, chronic renal failure, glomerular filtration rate, dialysis, dosing adjustment, Renal dysfunction, Renal impairment.